Grape seed proanthocyanidin extracts prevent high glucose-induced endothelia dysfunction via PKC and NF-κB inhibition. Issue 9 (2nd September 2015) - Jiang, Yanfei; Li, Yujie; Ding, Ye; Dai, Xiaoqian; Ma, Xiaotao; Bao, Lei; Zhang, Zhaofeng; Li, Yong
Abstract: In our study, it has been detected in vivo and in vitro that GSPE reversed high glucose-induced the increase of ICAM-1 and VCAM-1. It is shown that by western blotting detection, GSPE significantly inhibited the activation of NF-κB induced by high glucose while there was significant decrease of the expression of PKC with GSPE intervention. By adding the NF-κB blocker PDTC and the PKC inhibitor peptide 19–31(10 −6 M), no significant difference was found in the levels of VCAM-1 and ICAM-1 among GSPE group, the PKC inhibitor peptide 19–31-added GSPE group and the PDTC-added GSPE group. So the conclusion could be drawn that PKC inhibition must be involved in GSPE decreasing the level of ICAM-1 and VCAM-1.We proved for the first time that GSPE prevented high glucose-induced the increase of ICAM-1 and VCAM-1 by PKC and NF-κB inhibition. These findings show a novel mechanism of the action GSPE preventing endothelial dysfunction, which may have clinical application values. Graphical abstract: : Structural analyses have elucidated the reaction mechanisms of enzymes with potential bioindustrial and/or bioremedial uses.